Diálogo sem o eu? : estudo da inversão pronominal na fala de duas crianças autistas - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
This work is inserted in the studies on language acquisition by problematizing linguistic characteristics in the speech of two autistic children, more specifically the inversion of the pronoun "I" by "he" / "she" or by the proper name. One of the main objectives is to analyze the status of the other / Other in the process of dialogical interaction. The study makes a theoretical intersection between linguistics, psychoanalysis and speech therapy (language clinic). The reflections are based mainly on the works of Saussure (2006), when discussing the possible place for the study of pronouns between the constructs on language and speech; in Benveniste (1988, 1989), in the search to unveil the function of personal pronouns in the process of subjectification in relation to language / discourse; in Lacan (1985, 1992, 1998a, 1998b, 1998c, 1998d, 1998e), regarding the psychic formation of the “I” and the status of subject / language / other involved in the subjective constitution of the speaker; in Lemos (1981, 1982, 1986a, 1986b, 1994, 1995, 1998, 2000a, 2000b, 2001, 2002a, 2002b, 2003, 2004, 2006), to discuss the three subjective positions necessary to capture the language. The methodology is based on the qualitative paradigm and on the theory grounded in data (GLASER; STRAUSS, 2006), and has as premise the “listening” of the circumscribed singularity in the constitution of interactive dialogues between the therapist and the children. In this study, autism is analyzed with a focus on the subjective constitution of the subjects. The hypothesis of the study is that the inversion of the personal pronoun "I" marks confusions, hesitations and singular occultations, which can "fracture" the linguistic functioning and, likewise, interfere in the change of subjective positions before the language, culminating in changes in person / space / time referentiality. The results showed that, in the speech of the two children, there is a distance in relation to the speech of the other (alienation from the other / subjective first position), with fixation on the dominant pole of the language (second position) and rare constructions of self-speech (third position). It is understood that this research contributes to the discussions around the linguistic phenomenon studied, insofar as the inversion of the personal pronoun “I” has a hybrid and interdisciplinary origin.
Keywords: Autismo; Aquisição de linguagem; Interação dialógica; Pronomes pessoais; Autism; Language acquisition; Dialogic interaction; Personal pronouns; LINGUISTICA, LETRAS E ARTES::LETRAS